2019
DOI: 10.1126/sciadv.aaw1462
|View full text |Cite
|
Sign up to set email alerts
|

Metal-insulator transition in a semiconductor nanocrystal network

Abstract: Many envisioned applications of semiconductor nanocrystals (NCs), such as thermoelectric generators and transparent conductors, require metallic (nonactivated) charge transport across an NC network. Although encouraging signs of metallic or near-metallic transport have been reported, a thorough demonstration of nonzero conductivity, σ, in the 0 K limit has been elusive. Here, we examine the temperature dependence of σ of ZnO NC networks. Attaining both higher σ and lower temperature than in previous studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…Metallic nanoparticles, including elemental metals and doped semiconductors, hold promise as solution-processable building blocks to prepare conducting materials, from metallic interconnects to transparent conducting films and electrocatalytic aerogels. But such materials exhibit wide-ranging transport properties and often their conductivity is thermally activated, implying they are in fact insulators. Unless the nanocrystals are fused into bulk metals, for example, by thermal annealing, conventional metallic behavior has rarely been observed. , In such cases, conductivity decreases as temperature increases since phonon scattering limits the electron mobility. Between these two limits, nanostructured materials may be metallic, meaning their conductivity approaches a finite, nonzero value in the low-temperature limit, but still have an unusual negative thermal coefficient of resistivity (TCR). , Although strengthening electronic coupling, by using solution- or vapor-phase deposition to fill the spaces between metal oxide nanocrystals ,, or replacing long insulating ligands with shorter ones, ,, is known to increase conductivity, criteria determining the temperature-dependent transport behavior remain the subject of intense investigation. …”
Section: Preparation and Characterization Of Nanocrystal Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Metallic nanoparticles, including elemental metals and doped semiconductors, hold promise as solution-processable building blocks to prepare conducting materials, from metallic interconnects to transparent conducting films and electrocatalytic aerogels. But such materials exhibit wide-ranging transport properties and often their conductivity is thermally activated, implying they are in fact insulators. Unless the nanocrystals are fused into bulk metals, for example, by thermal annealing, conventional metallic behavior has rarely been observed. , In such cases, conductivity decreases as temperature increases since phonon scattering limits the electron mobility. Between these two limits, nanostructured materials may be metallic, meaning their conductivity approaches a finite, nonzero value in the low-temperature limit, but still have an unusual negative thermal coefficient of resistivity (TCR). , Although strengthening electronic coupling, by using solution- or vapor-phase deposition to fill the spaces between metal oxide nanocrystals ,, or replacing long insulating ligands with shorter ones, ,, is known to increase conductivity, criteria determining the temperature-dependent transport behavior remain the subject of intense investigation. …”
Section: Preparation and Characterization Of Nanocrystal Filmsmentioning
confidence: 99%
“…8−13 Unless the nanocrystals are fused into bulk metals, for example, by thermal annealing, conventional metallic behavior has rarely been observed. 2,9 In such cases, conductivity decreases as temperature increases since phonon scattering limits the electron mobility. Between these two limits, nanostructured materials may be metallic, meaning their conductivity approaches a finite, nonzero value in the low-temperature limit, but still have an unusual negative thermal coefficient of resistivity (TCR).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Greenberg et al [ 46 ] expanded on these studies. They showed that the electronic properties of plasma‐deposited ZnO nanocrystal films (Figure 3a,b) could be modified to enable metallic conduction by applying the following measures, in part illustrated in Figure 3c: (a) photonic sintering through intense pulsed light exposure to grow the nanocrystal‐nanocrystal contact facet; (b) ALD deposition of ZnO to further grow the contact facet radius; (c) ALD of Al 2 O 3 to remove electron trap states on the ZnO network; and (d) additional photodoping to raise the carrier concentration.…”
Section: Turning Nanocrystal Films Into Nanocomposites and Improving mentioning
confidence: 99%
“…Curves above the green curve represent metallic conduction, below the green curve hopping conduction. (a–d) Reproduced with permission from Greenberg et al [ 46 ]…”
Section: Turning Nanocrystal Films Into Nanocomposites and Improving mentioning
confidence: 99%